RANCANG BANGUN APLIKASI GAME EDUKASI PENGENALAN HURUF ALFABET DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Wicaksana, Rizki Alief; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2020)
Educational games have very high potential for increasing motivation in learning process. Besides increasing motivation, educational games also have advantages compared to e-learning methods, easier to understand and more interesting. The design of this game will prioritize the process of teaching and learning using the concept of "playing while learning". For some children, "Learning" feel very boring, so that with educational games created as attractive as possible, children will not realize if what is being done is learning and children will enjoy the learning process. The method used in the design of this Android-based learning alphabet education game are System Development Life Cyle (SDLC) Waterfall and Unified Modeling Language (UML) method, this game made with Unity 3D software, assisted with Adobe Photoshop, Blender and Vuforia SDK. it expected this educational game using augmented reality technology on the android platform can increase children's learning interest. This technology allows displaying three dimensional animation in real time that seems real.